1981
DOI: 10.1002/ijc.2910270310
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of natural killer cell activity in patients with chronic lymphocytic leukemia

Abstract: Natural killer (NK)6 cell activity of peripheral blood lymphocytes against human leukemia cell lines was measured in patients with chronic B-cell lymphocytic leukemia (CLL) and age- and sex-matched controls. In order to remove the leukemia cells that interfere with the in vitro assay we (1) isolated lymphocytes that form rosettes with sheep red blood cells (SRBC) or (2) lysed the CLL cells with a monoclonal anti-B cell antibody and complement. NK activity in either lymphocyte preparation from nine of 10 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(79 citation statements)
references
References 22 publications
(12 reference statements)
7
69
0
2
Order By: Relevance
“…Poor expression of CD69 was also observed on CD16 þ CD56 dim NK cells from CLL patients; this deficit could explain the previously reported reduction in NK cytotoxic activity in the absence of exogenous stimulation. 15,28 This relative NK-cell anergy could be due to the ability of CLL cells and their microenvironment to produce cytokines, such as IL-10, which suppress the proliferation of antigen-specific Th1 cells and downregulate co-stimulatory molecules on antigen-presenting cells. [29][30][31] Importantly, NK-cell function was perfectly recovered following activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor expression of CD69 was also observed on CD16 þ CD56 dim NK cells from CLL patients; this deficit could explain the previously reported reduction in NK cytotoxic activity in the absence of exogenous stimulation. 15,28 This relative NK-cell anergy could be due to the ability of CLL cells and their microenvironment to produce cytokines, such as IL-10, which suppress the proliferation of antigen-specific Th1 cells and downregulate co-stimulatory molecules on antigen-presenting cells. [29][30][31] Importantly, NK-cell function was perfectly recovered following activation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies have reported functional alterations in NK cells in these patients, including defective cytotoxic activity, which are particularly pronounced in advanced disease and that could be because of the accumulation of leukemic cells rather than to any intrinsic defect in the former. 15,16 This hypothesis was suggested by the restoration of their functional activity after interferon (IFN)-a and/or interleukin (IL)-2 treatment. 17,18 We conducted the first extensive characterization of the phenotypic and cytotoxic qualities of NK cells from CLL patients and compared them with those of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, triggering of NK cell cytotoxicity reflects a balance between activating and inhibitory signals mediated by cell-surface receptors that belong to several different gene families. [12][13][14][15] In B-CLL patients, several phenotypic and functional alterations in NK cells 16,17 have been described such as defective cytotoxic activity. [16][17][18][19] The reason as to why NK activity is low in most patients with CLL is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The NK cell activity was not detectable in patients with advanced disease and six times lower than control in patients with early disease. 28 This finding, however, has been challenged by others. 29 To test whether CLL NK cells would be capable of mediating an effective response with SMIP-016 GV , we used NK cells from patients with early stage disease as effectors in ADCC assays against Raji cells targets.…”
Section: Resultsmentioning
confidence: 98%